Television and film studies in Indonesia: A bibliometric analysis - Ratnasari, Eny; Mahameruaji, Jimi Narotama; Bantugan, Brian; Adi, Achwan Noorlistyo (ProTVF, 2025)
Background: Television and film research must be continuously updated due to media convergence. Moreover, Indonesia experienced an analog switch-off event that changed how television viewers consume television shows. Furthermore, the pattern of Indonesian film consumption has also changed since the existence of over-the-top streaming platforms, which have continued to grow. Purpose: This study aims to conduct bibliometric research on articles in the ProTVF Journal published from 2017 to 2024. Methods: This study analyzes 107 articles in the ProTVF Journal from the Google Scholar and Dimension database between 2017 and 2024. This study uses VOSviewer, Dimension, and Litmaps to assist in visualization and analysis. Results: Articles in the ProTVF journal were dominated by qualitative methods, followed by quantitative and mixed methods. Among the qualitative methods, qualitative descriptive techniques are the most frequently used, followed by semiotic and discourse analysis. Then, there are five main topics: television studies, media convergence, analysis of television shows in the Indonesian context, audience research, and the young generation as viewers in the digital era. Conclusion: The publication trend in the ProTVF Journal increased from 2017 to 2024. Based on the focus on television or film, research focusing on films is higher than research related to television. Implications: This study is the first bibliometric study to comprehensively describe articles published in the ProTVF Journal since its establishment. The results can help film, television, and media researchers understand research trends, find research collaborators, and optimize the choice of research topics. Further research will likely involve scientific collaboration between authors from various institutions, especially policymakers in Indonesia's broadcasting, advertising, and film industries.